Vitamin D status, hypertension and body mass index in an urban black community in Mangaung, South Africa - Ronette Lategan; Violet L. van den Berg; Jasminka Z. Ilich; Corinna M. Walsh (AOSIS, 2016)
Background: A strong relationship exists between hypertension and body weight. Research has linked both higher blood pressure and body weight with lower vitamin D status. Objective: This study assessed the vitamin D status of a low-income, urban, black community in South Africa, to examine whether serum levels of 25-hydroxy vitamin D [25(OH)D] are associated with hypertension and body mass index (BMI). Methods: Data collected from 339 adults (25-64 years) from the Assuring Health for All in the Free State (AHA-FS) study were analysed. Variables measured include serum 25(OH)D, blood pressure, weight and height to determine BMI, and HIV status. Results: Mean 25(OH)D level was 38.4 ± 11.2 ng/mL for the group; 43.5 ± 11.8 ng/mL and 37.0 ± 10.6 ng/mL for males and females, respectively. Approximately 40% of the participants were HIV-positive and 63.4% hypertensive. Based on BMI, 11.8% were underweight, 33.0% normal weight, 23.0% overweight and 32.1% obese. HIV status showed no correlation with 25(OH)D levels when controlling for BMI. Poor inverse relationships were found between BMI and 25(OH)D (p = 0.01), and between mean arterial blood pressure and 25(OH)D (p = 0.05). When controlling for BMI, no correlation was found between 25(OH)D and the prevalence of hypertension or mean arterial blood pressure. Conclusion: Approximately 96% of participants had an adequate vitamin D status, which could be attributed to latitude, sunny conditions and expected high levels of sun exposure because of living conditions. Results confirmed a poor inverse relationship between vitamin D status and hypertension, which seems to be dependent on BMI.